Sistem Monitoring Volume Sampah Medis Berdasarkan Ketinggian Menggunakan Sensor Ultrasonik Berbasis IoT dengan Notifikasi Telegram - Fauzi Ramdani; Nuroji Nuroji (Journal of Information System Research (JOSH), 2026)
This research aims to develop an Internet of Things (IoT)-based medical waste height monitoring system as an effort to overcome the problem of manual medical waste monitoring in small-scale health facilities. This condition has the potential to cause delays in waste transportation, thereby increasing health risks and environmental pollution. The developed system utilizes a NodeMCU ESP8266 microcontroller as the main control unit, an HC-SR04 ultrasonic sensor to measure the height of medical waste piles, and a 16x2 I2C LCD as a real-time information display medium. If the waste height reaches a predetermined limit, the system automatically sends a warning notification via the Telegram application. The research method used is Research and Development (R&D) with an experimental approach that includes the stages of problem identification, system design, implementation, and tool testing. The test results show that the ultrasonic sensor has an accuracy level of 98% with an average error difference of ±2 cm, and the Telegram notification delivery time is less than 5 seconds after the threshold is reached. The contribution of this research lies in the design and implementation of a simple, real-time, and easy-to-implement IoT-based medical waste volume monitoring system, so that it can support safer, more effective, and more responsive medical waste management in small-scale health facilities.